(untitled) (Samriddhi Journal of Development Studies, 2025)
People have settled in Kathmandu valley for more than 3000 years. Through the course of time, people living in the valley have developed and advanced several types of water infrastructures for collection, distribution and delivery of water to the settlements. Among these traditional water infrastructures inventory of these Stone spouts and Ponds have recently been prepared. In the inventory, details of the location, measurement, state of existence, use cases and many other headings have been presented, although individually and in isolation from the collective context. Studying all of them in collective context has potential to yield new information on the choice of site for construction on the basis of various requirements, accumulation in one particular area, hint of historical settlement and so on. Both qualitative and quantitative methods will be used for the study. Inventory of the water infrastructures are invaluable data source. Data from this inventory is mapped and analyzed on the basis of the location in particular terrain and space as well as concentration of ponds and stone spouts in any particular area. The results from this analysis are interpreted in their historical context using utilitarian, religious, ethnological perspectives. From this research, it is found that most of the stone spouts and ponds are located at the slope/bottom of the bluff/hill because of the ease of access of water. And majority of stone spouts are located in agricultural fields/new settlements whereas most ponds are located in historical areas. The outcome from this study will be useful for understanding the overall traditional water infrastructure of Kathmandu valley.